Application of an offshore wind farm layout optimization methodology at Middelgrunden wind farm. (15th July 2017) - Pillai, Ajit C.; Chick, John; Khorasanchi, Mahdi; Barbouchi, Sami; Johanning, Lars
Abstract: This article explores the application of a wind farm layout evaluation function and layout optimization framework to Middelgrunden wind farm in Denmark. This framework has been built considering the interests of wind farm developers in order to aid in the planning of future offshore wind farms using the UK Round 3 wind farms as a point of reference to calibrate the model. The present work applies the developed evaluation tool to estimate the cost, energy production, and the levelized cost of energy for the existing as-built layout at Middelgrunden wind farm; comparing these against the cost and energy production reported by the wind farm operator. From here, new layouts have then been designed using either a genetic algorithm or a particle swarm optimizer. This study has found that both optimization algorithms are capable of identifying layouts with reduced levelized cost of energy compared to the existing layout while still considering the specific conditions and constraints at this site and those typical of future projects. Reductions in levelized cost of energy such as this can result in significant savings over the lifetime of the project thereby highlighting the need for including new advanced methods to wind farm layout design. Abstract : Highlights: Application of both a genetic algorithm and particle swarm optimizer to design and optimize offshore wind farm layouts at Middelgrunden. Wind farm layouts designed using 3 different levels of constraint which are of interest to wind farm developers. Various degrees of constraint allow the impact of these constraints to be quantified and compared. Presentation of six new layout for Middelgrunden with reduced LCOE compared to the as-built case.